Comparison thermochemical and thermophysical performances analysis in laser processing by dynamic heat-matter diffusion coupling simulation and corresponding experiment validation. Issue 3 (15th February 2020) - Li, Wenzhi; Gao, Yinjun; Ma, Zhuang; Gao, Lihong; Wei, Chenghua; Wang, Fuchi; Wu, Taotao; Wang, Lijun; Li, Hezhang
Abstract: The laser-matter interaction contains complex thermophysical and thermochemical responses. The variation of energy and composition happen in thermophysical and thermochemical process will totally change the interaction behaviors. In order to obtain an accurate mechanism and promote the understanding of laser-matter interaction, all thermophysical and thermochemical responses, especially the thermochemical part, should be considered and investigated. In this study, a coupled heat-matter diffusion model based on thermodynamic chemical equilibrium finite-element method and thermochemical ablation theory was established. The materials with complex reaction enthalpy change in high temperature environment were chosen to validate the model. The results show that this model is accurate, as the maximum error of back-surface temperature response is just 4.0% between experimental and calculation values. The detailed variations of composition, temperature and optical reflection were obtained and analyzed, which is in good agreement with the experiment. This coupled heat-matter diffusion model including all thermophysical and thermochemical response has the great potential in nearly all laser-matter interaction involved application.